DEVELOPMENT OF HIGH SCHOOL STUDENTS BASED ON CRITICAL THINKING ABILITY IN ECOSYSTEM CONCEPT - Nuril Maulidya Hapsari; Bunda Halang; Mahrudin Mahrudin (ATRIUM PENDIDIKAN BIOLOGI, 2021)
One of the learning tools that need to be developed, so that the objectives of the 2013 curriculum are achieved, one of which is the Student Worksheet. The Student Worksheet is one of the learning media that can help students to be more active in constructing their knowledge according to the demands of the curriculum. Critical thinking is the ability to give reasons in an organized manner, and evaluate the quality of a reason systematically. The ability to think critically can help the problem-solving process, simplify work, and be able to determine the relationship of something to another more accurately. This study aims to produce high school Biology worksheets based on valid critical thinking skills on Ecosystem material. This development uses the Tessmer design, which consists of (1) self-evaluation stages, (2) expert reviews, and (3) individual tests. Validation was carried out by 3 experts (2 lecturers and 1 teacher). The results showed that the product validity has a valid category, with an overall average of 3.58 declared valid, and based on expert tests it has a content practicality category with an average of 3.85, declared good.